Application of the grading system for dental casts and panoramic radiographs - ABO/OGS in orthodontics: a topic review - Sandra Patricia Castaño-Duque; Andrés Felipe Hernández-Pantoja; María Inés Lemos-Torres (Universidad de Antioquia, 2024)
In the last years, clinicians and researchers have evaluated orthodontic treatment outcomes through intraoral examination or the use of indices. One of the most frequently used indices is the Grading System for Dental Casts and Panoramic Radiographs System (CRE). A literature search was carried out in different databases such as PubMed, Embase, Lilacs, Cochrane, and other sources, through a structured strategy using keywords and Boolean operators. The references that met the search criteria and the researchers' examination were obtained in full text, classified, and analyzed to collect information on the 4 set out topics: 1. CRE (ABO/OGS) in the evaluation of the quality of results, 2. CRE (ABO/OGS) and other indices, 3. CRE (ABO/OGS) digital implementation, 4. CRE (ABO/OGS) regional implementation. 103 articles were found, of which 52 were selected. The use of CRE worldwide was observed, showing that it is a versatile tool in multiple fields, such as analysis of therapeutic management, type of equipment used, measurement stability, performance of university and private services, among other topics aimed at knowing the result of orthodontic treatment. From other part, its use along with other indices seems to be a complement that would allow analysis of dental, skeletal, and facial variables not contemplated. The digital implementation of the CRE (ABO/OGS) shows to be a promising tool that after adjustments can bring advantages in the analysis of results. Likewise, it has been found that the use of CRE (ABO/OGS) within universities has generated improvement in treatment results when compared over time.